The evaluation model on an application of sroi for sustainable social enterprises - Dong-Joo Kim; Yong-Seung Ji (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The evaluation of social enterprises has been criticized for not being able to reflect the positive social aspects of the company through the financial evaluation. SROI (Social Return on Investment) is a social concept applied to the measurement of economic return on investment that aims to measure the social added value of social enterprises and reflect them in their performance. It is necessary to research for the provision of support and management for sustainable social enterprises, and to prepare a method for evaluating social enterprise by applying SROI. The Delphi 1st and 2nd surveys for the development of evaluation model for social enterprises using SROI were conducted by 50 social enterprise CEOs and experts. To produce the results of this study, the SPSS 20.0, AMOS 24 and Expert Choice 11 programs were used and the pairwise comparison analysis method was performed to analyze importance and priority. The results of the Delphi and AHP (Analytic Hierarchy Process) analysis showed that employment was the most important factor in social enterprises with the highest share of newly hired personnel. Employment-type social enterprises have the highest priority in terms of employment, income (income increase for vulnerable workers), and community contribution (affordable of social services), while the social service type was in order of employment, community contribution, and income (income increase for the vulnerable workers). On the other hand, the mixed type was employment (newly hired personnel), income (income increase of vulnerable workers), employment (social work participants' switch to similar work after contract expiration), and community contribution (affordable of social services). This study makes efforts to form social capital by raising the public's awareness of social value with efficient management through various evaluations of social enterprises and the emergence of various social enterprises. This study also emphasizes the need to better understand social enterprises as a multi-scholar and multi-dimensional organization that includes a multi-faced mechanism of social, economic, and environmental community development, away from understanding social enterprises as a specific business model.
Keywords: 650; AHP; delphi; SROI; sustainable social enterprises